Understanding the twist-bend nematic phase: the characterisation of 1-(4-cyanobiphenyl-4′-yloxy)-6-(4-cyanobiphenyl-4′-yl)hexane (CB6OCB) and comparison with CB7CB. Issue 32 (22nd July 2016) - Paterson, Daniel A.; Gao, Min; Kim, Young-Ki; Jamali, Afsoon; Finley, Kirsten L.; Robles-Hernández, Beatriz; Diez-Berart, Sergio; Salud, Josep; de la Fuente, M. Rosario; Timimi, Bakir A.; Zimmermann, Herbert; Greco, Cristina; et al.
Abstract : The design and characterisation of the nonsymmetric liquid crystal dimer, 1-(4-cyanobiphenyl-4′-yloxy)-6-(4-cyanobiphenyl-4′-yl) hexane (CB6OCB) is reported. Abstract : The synthesis and characterisation of the nonsymmetric liquid crystal dimer, 1-(4-cyanobiphenyl-4′-yloxy)-6-(4-cyanobiphenyl-4′-yl)hexane (CB6OCB) is reported. An enantiotropic nematic (N)–twist-bend nematic (NTB ) phase transition is observed at 109 °C and a nematic–isotropic phase transition at 153 °C. The NTB phase assignment has been confirmed using polarised light microscopy, freeze fracture transmission electron microscopy (FFTEM), 2 H-NMR spectroscopy, and X-ray diffraction. The effective molecular length in both the NTB and N phases indicates a locally intercalated arrangement of the molecules, and the helicoidal pitch length in the NTB phase is estimated to be 8.9 nm. The surface anchoring properties of CB6OCB on a number of aligning layers is reported. A Landau model is applied to describe high-resolution heat capacity measurements in the vicinity of the NTB –N phase transition. Both the theory and heat capacity measurements agree with a very weak first-order phase transition. A complementary extended molecular field theory was found to be in suggestive accord with the 2 H-NMR studies of CB6OCB-d2, and those already known for CB7CB-d4 . These include the reduced transition temperature, T NTB N / T NI, the order parameter of the mesogenic arms in the N phase close to the NTB –N transition, and the order parameter with respect to the helix axis which is related to the conical angle for the NTB phase.